Implementation of Inverse Kinematic and Trajectory Planning on 6-DOF Robotic Arm for Straight-Flat Welding Movement - Muhammad Arif Nur Huda; Sugeng Hadi Susilo; Pribadi Mumpuni Adhi (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Robotic arms have been used in various processes such as for moving goods, welding, assembling, and painting. In the case of welding and painting, it is necessary to move the end-effector robot accurately and smoothly to follow the specified trajectory. In robotic arm control, 2 things are important to be analyzed and implemented in controlling the motion of the robotic arm, namely inverse kinematic and trajectory planning. In this study, the inverse kinematic and trajectory planning algorithms are implemented to the robotic arm controller in the form of an Arduino Mega 2560 microcontroller. The inverse kinematic solution uses geometric and algebraic analytical methods. while the trajectory planning method is using LSPB (Linear Segment Parabolic Blend) Trajectory in Cartesian Space. Data retrieval is done by giving 2 input coordinates of the desired position and orientation, then the data in the form of the joint angle value will be measured using a rotary encoder as an angle sensor. Furthermore, the joint angle measurement value is converted in cartesian coordinates to get the end-effector position. Data analysis is done by comparing the data value of each joint angle with the calculated value so that the error value appears. The results showed that the inverse kinematic and trajectory planning algorithms were successfully applied to the 6-DOF robotic arm to perform straight-flat welding movements. Inverse kinematic testing on both input coordinates, the average error value for joints 2, 3, and 5 is 1.82º, 1.26º, and 2.08º. Meanwhile, the average error of the end-effector position at the x and z coordinates is 2.08 mm and 12.9 mm, respectively. Then for the trajectory planning test, the error value for the end-effector position in the x and z coordinates is 2.25 mm and 10.7 mm.